Integrasi Total Quality Management dan Nilai Islam dalam Pengembangan Mutu Pendidikan Islam - Askini Ainul Fithri; Moh. Ali (CV. Global Cendekia Inti, 2026)
The lack of integration between the principles of total quality management (TQM) and Islamic values in the governance of educational institution is a major issue hindering quality development in Islamic education. Thin condition has a terrible impact on the achievement of educational quality which is not only academically excellent, but also morally and spiritually robust. This study aims to analyze in-depth the integration of TQM and Islamic values in the development of quality in Islamic education. A qualitative method with a literature review approach was employed to this study, utilizing academic literature as a data source. Thematic analysis was conducted to identify the patterns or themes within the literature. The findings reveal that the principles of TQM such as customer satisfaction, continuous improvement, and leadership involvement show significant relevance to Islamic values such as ihsan, itqan, amanah, and istiqamah. The integration of these two domains generates a conceptual model encompassing value-based leadership, Islamic quality culture, integrative learning process, continuous evaluation, and stakeholder involvement. Overall, the integration of TQM and Islamic values has significant implications for the development of holistic and sustainable Islamic education quality, which is fundamentally oriented toward the formation of students’ morality and spirituality.